ANALISIS PENGARUH UKURAN PERUSAHAAN, TINGKAT PROFITABILITAS, TINGKAT LIKUIDITAS, DAN PROPORSI SAHAM PUBLIK TERHADAP PENGUNGKAPAN SUKARELA PADA PERUSAHAAN PROPERTY & REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pieter Nainggolan (Jurnal Akuntansi Bisnis, 2017)
As a form of accountability to investors, the company would have to disclose the information in the form of the disclosure which he did both compulsory and voluntary disclosure disclosure. For that I need to know what are the factors that affect its extensive disclosures made a voluntary disclosure primarily corporations.Regression test that has been made available that the size of the company and the proportion of public shares of influential significantly to widespread voluntary disclosure. While the level of profitability and liquidity rate did not affect significantly to broad disclosure is voluntary. To test together (with a coefficient of determination) found that the independent variables have an influence equal to 26% of the area of voluntary disclosure.So too with the greater proportion of shares owned by the public, the company will likely make a voluntary disclosure. This is in contrast to the level of profitability and liquidity. The companies that have a level of profitability and liquidity is not great bail these companies have extensive voluntary disclosure. Keywords : Total Assets, ROE (Return On Equity), Current Ratio, The Proportion Of Public Shares, Voluntary Disclosure